(untitled) (La Universidad, 2016)
The ancient Maya village of Cerén is located in west-central El Salvador and is situated on a terrace west of the Río Sucio in the Zapotitán Valley .Questions remain unanswered about ancient Maya subsistence, particularly the role that root crops such as manioc played. Lack of material evidence for Classic Period Maya (AD 250-800) agriculture has been identified as one of the key restricting factors in advancing our understanding of these practices. Thus, the evidence for cultivation from Cerén, El Salvador affords a remarkable opportunity to examine ancient Maya agriculture and to produce a more accurate reconstruction of this community’s subsistence system. This paper specifically focuses on the latest data and interpretations of manioc cultivation at a Classic Maya site.